Draft Integrated Annual Plan for Darjeeling Hill Areas 1987-88 Volume - I and II Government of West Bengal - Planning Commission (Planning Commission, 1987)
The proposed Annual Plan 1987-88, for the area, has been drawn up with the basic objective of achieving economic and social development keeping in view the need to maintain and improve ecological balance. In keeping with the recommendations of the Report of the Working Group on Hill Area Development for the Seventh live Year plan, the developmental activities will be geared towards achievement of basic needs such aa food, fuel, water supply, health, education and fodder for livestock and essential basic infrastructure.
Government of West Bengal, Development and Planning Department